Potensi Tenun Ikat Sebagai Sumber Belajar Berbasis Etnosains - Riantina Fitra Aldya; Elga Djarawula; Adriana Rewa Malo; Yuswa Istikomayanti (Jurnal Ilmiah Biosaintropis (Bioscience-Tropic), 2023)
Traditional knowledge seems to be the opposite of modern knowledge. In this position, the knowledge of the local community, especially in weaving works, is the result of processing the ancestral knowledge of the Sumba tribe in East Nusa Tenggara. This study aims to describe the potential of woven ikat not only as a work but also the culture of the people of Sumba as a teaching resource in schools. Ethnoscience is expected to become a bridge between science and culture approaches for students in the 21st century. This research is a type of ethnographic research with an interpretive design. Several methods, namely the in-depth interview method and the literature review method. In-depth interviews were used to explore the potential of Ikat weaving and literature analysis as secondary data in the study of student teaching materials. The study of Ikat weaving as a source of teaching materials includes aspects of coloring techniques, weaving techniques, and ethnomathematics of weaving motifs. The results of this study serve as reference material for learning in schools not only in local content subjects but can be integrated into the core content of Science/Science as well as Mathematics and other subject areas in formal schools.